ANALISIS KIMIA BATANG AREN (ARENGA PINNATA MERR) YANG BERASAL DARI CIANJUR DAN ANALISIS PENDAHULUAN KAYU AREN YANG BERASAL DARI SUMATERA BARAT - Gusmailina Gusmailina; Hartoyo Hartoyo (Jurnal Penelitian Hasil Hutan, 1991)
This article describes  about  Chemical  analysis of aren stem  (Arenga  pinnata  Mcrr) from   Cianjur  and preliminary   analysis aren wood from   West Sumatera.   The analysis comprised  of the determination    of holocelluloce,  lignin, pentosan,   tannin,  ash content,  silica content,  and the solubility  in cold  water,  hot  water,  one  percent  of sodium   hydroxide   and  alcohol-benzene   extractives.   The  analysis  were conducted   to determine  the chemical  component   of  aren stem from  Jasinga,   Bogor  and  chemical  component   of  coconut  wood.The average of holocelluloce,   lignin,  pentosan,   tannin,  ash and silica, extractives content,  solubility  in sodium  hydroxide   of peripheral portion  for  aren stem from   Cianjur  were consecutively   as follow:    67,79  %,  22,17  %,  19,43 %,  4,07  %,  0,94  %,  0,67  %,  5,62  %  (in hot water),  5, 14 % (in cold  water),  2,69  % (in alcohol-benzene),    24, 79 % in sodium   hydroxide   1   %.   While for  the central portion,   the above analysis  showed   averages  as follow   :  48,07  %,  22,95  %,  19,3  %,  16,98  %,  4,41  %,  3,92  %,  17,51  % (in hot  water),  12,81  % (in cold water),  7,83  %  (in akohol   benzene),   31,12  % in sodium   hydroxide   1   %.The average of holocelluloce,   lignin, pentosan,   tannin,  ash and silica, extractives content,  solubility  in sodium  hidroxide.  of  aren wood (peripheral  portion)  for  63,93  %,  27,08  %,  11,17 %,  5,12  %,   1,50   %,   0,99  %,  1,02 %  (in cold  water),  2,99  %  (in hot  water) 4,50  %  (in alcohol-benzene),   28,69  % in sodium  hydroxide.   While for  the ruyung  enau,  the above  analysis showed  averages as follow  :  68,83  %,  22,93 %,  14,0  %,  5,78  %,  1,25  %,  0,92  %,  0,22  %  (in cold  water),  3,01  %  (in hot  water),  3,98  %  (in alcohol-  benzene),   35,57  %  in sodium hydroxide.Based  on  chemical  analysis  and  the comparison   to the coconut  wood  gave  a low pentosan  and  ash content from   coconut  wood.  On the contrary  had  a high  tannin,  extractives  and silica content  to coconut  wood.